TRAFFICO DI ESSERI UMANI NELLA PROSPETTIVA BIBLICA DELL’ANTICO TESTAMENTO - Abatan, Yofince; Abatan, Kasmirus; Boymau, Yerliani (STIPAS Keuskupan Agung Kupang, 2024)
Crimes committed by certain individuals, such as human trafficking, are a serious problem that needs to be addressed and continuously voiced and solutions sought, because these acts are sins that injure the human person himself and are also sins in front of them. human trafficking reduces the value and dignity of humans who are the face and likeness of God into goods that can be bought and sold. This action directly goes against God, who essentially loves humans and created humans equal to His own face and likeness. The aim of the research is for people to understand that this act of human trafficking already has the spirit of the Old and New Testaments. By understanding that humans are the image of God himself, solutions should be found to overcome the crime of human trafficking. This research uses a qualitative method by means of library research, namely investigating Bible stories, documents, theological books, articles, news related to the problem. The results of this research show that it is necessary to understand humans theologically in order to prevent and overcome cases of human trafficking in several ways, namely: humans as the image and likeness of God, humans were created as social creatures, humans were created not as goods but as individuals. As a follow-up, this research recommends that the government, church and society can make efforts to stop the practice of human trafficking which continues to grow.